Perbedaan Keterampilan Menulis Teks Deskripsi Menggunakan Model Think Talk Write Berbantuan Media Audio Visual dan Media Gambar - Marlisa, Welli; Karmila, Karmila; Kusumanegara, Afdhal; Suliman, Mohd Saipuddin; Costantino, Antonio (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2025)
The results of the descriptive writing skills test show that many students are still below the minimum passing grade (KKM). This is because students are not yet able to describe an object in detail. This study is a quantitative study using a quasi-experimental method. The design used is Nonequivalent Control Group Design. This study to have included a population of 280 seventh-grade students at SMPN 8 Sungai Penuh. The sampling process to have been conducted using specific criteria, applying a purposive sampling approach. The samples in this study were classes VII3 and VII4, with 35 students in each class. The instrument used in this study was a descriptive text writing skills test. The following are three conclusions from the data analysis. First, after the descriptive text writing skills test was conducted, students who were taught using Think Talk Write with audio-visual media obtained an average score of 85.57. Second, students taught using Think Talk Write with image media obtained an average score of 81.14. Third, there was a significant difference in the descriptive text writing skills of students taught using the Think Talk Write model with audio-visual media and image media.